2018
DOI: 10.3389/fimmu.2018.02914
|View full text |Cite
|
Sign up to set email alerts
|

Modulating T Cell Responses via Autophagy: The Intrinsic Influence Controlling the Function of Both Antigen-Presenting Cells and T Cells

Abstract: Autophagy is a homeostatic and inducible process affecting multiple aspects of the immune system. This intrinsic cellular process is involved in MHC-antigen (Ag) presentation, inflammatory signaling, cytokine regulation, and cellular metabolism. In the context of T cell responses, autophagy has an influential hand in dictating responses to self and non-self by controlling extrinsic factors (e.g., MHC-Ag, cytokine production) in antigen-presenting cells (APC) and intrinsic factors (e.g., cell signaling, surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 257 publications
3
33
0
Order By: Relevance
“…Stimulation of T lymphocyte receptors or HIV infection induces autophagy activation in vitro. The study found that thymic epithelial cells in the thymic cortex of mice have high levels of autophagic activity, suggesting that autophagy plays a role in the development and selection of T lymphocytes (Merkley et al 2018).…”
Section: Overviewmentioning
confidence: 90%
“…Stimulation of T lymphocyte receptors or HIV infection induces autophagy activation in vitro. The study found that thymic epithelial cells in the thymic cortex of mice have high levels of autophagic activity, suggesting that autophagy plays a role in the development and selection of T lymphocytes (Merkley et al 2018).…”
Section: Overviewmentioning
confidence: 90%
“…In addition, although the percentage of CD4 + T cells was increased under treatment of CCL-34 and CCL-34 plus 3-MA, the functions of T cells in vivo were not examined in our study. Considering the critical role of autophagy in regulating T cell responses 6 , whether the functions of CCL-34-induced T cells are suppressed by 3-MA in vivo can be further explored in the future. Taken together, our data indicate that CCL-34 regulates both LPM and SPM functions and induces the percentage of CD4 + T cell which is similar to the immune stimulating response of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…above, autophagy regulates T cell responses via direct modulation of T cells and indirect modulation of APCs 6 . Therefore, autophagy-promoting agents may serve as potential vaccine/adjuvants candidates to enhance immune responses 24,25 .…”
mentioning
confidence: 98%
“…Autophagy also functions in the presentation of MHC class I-restricted antigens, which stimulate CD8 + T cells. Autophagy in APC can, therefore, greatly influence the responses of T cell subsets via both MHC I and II-dependent antigenic presentations [ 47 ].…”
Section: Autophagy and Immune Responsesmentioning
confidence: 99%